2009
DOI: 10.1007/bf03404345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Hepatitis B Educational ESL Curriculum for Chinese Immigrants

Abstract: Objectives According to recent census data, 1,216,600 Canadians are of Chinese descent, and over 80% of Chinese Canadians are foreign born. Approximately 10% of Chinese immigrants are chronic carriers of hepatitis B, compared with less than 0.5% of the general population. English as a second language (ESL) classes provide ready access for individuals with limited English proficiency who are not reached by English language health education materials and media campaigns. We conducted a group-randomized trial to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Furthermore, while we are aware of no published reports of TB programming at adult education centers, adult ESL programs have been successful venues for educational programming around the topics of hepatitis B [27], cancer screening and prevention [28], and cardiovascular health [29]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while we are aware of no published reports of TB programming at adult education centers, adult ESL programs have been successful venues for educational programming around the topics of hepatitis B [27], cancer screening and prevention [28], and cardiovascular health [29]. …”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, the Institute of Medicine (IOM) found that the main barriers to controlling HBV were lack of knowledge and awareness and insufficient support for prevention, control, and surveillance of the disease. 1 Numerous interventions have been developed and tested to address hepatitis B disparities among Asian Americans, including media campaigns, 10,11,12 lay health worker outreach, 13,14 community mobilization, 15 and church-based interventions. 16 However, no published research addresses the cost of outreach or efforts to maximize efficiency through less labor-intensive strategies.…”
Section: Hepatitis B: a Major Risk For Asian Americansmentioning
confidence: 99%
“…For example, Taylor et al. () undertook an RCT in Canada with Asian migrants to test an ESL curriculum designed to improve hepatitis B knowledge and screening. Results indicated significantly greater improvements in knowledge and behaviour in the treatment group.…”
mentioning
confidence: 99%